Synthesis and DNA-Binding Properties of the Ni(II) Complex with Tetraazamacrocyclotetradecane - Bi, Jian-Hong; Cui, Man (Asian Journal of Chemistry, 2011)
A tetraazamacrocyclotetradecane complex of Ni(II) with composition NiL(ClO4)2 (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazamacro-cyclotetradecane) was synthesized and characterized by elemental analysis and IR spectra. The reciprocities of the NiL(ClO4)2 with DNA were studied by cyclic voltammetry. In the presence of DNA, the redox peaks of NiL(ClO4)2 shifted to more negative values and the peak current decreased. The experimental results illustrate that the NiL(ClO4)2 could interact with DNA by electrostatic combining mode.